The selection function of the RAVE survey - Wojno, Jennifer; Grebel, Eva K. (Arxiv, 2017)
We characterize the selection function of RAVE using 2MASS as our underlying population, which we assume represents all stars which could have potentially been observed. We evaluate the completeness fraction as a function of position, magnitude, and color in two ways: first, on a field-by-field basis, and second, in equal-size areas on the sky. Then, we consider the effect of the RAVE stellar parameter pipeline on the final resulting catalogue, which in principle limits the parameter space over which our selection function is valid. Our final selection function is the product of the completeness fraction and the selection function of the pipeline. We then test if the application of the selection function introduces biases in the derived parameters. To do this, we compare a parent mock catalogue generated using Galaxia with a mock-RAVE catalogue where the selection function of RAVE has been applied. We conclude that for stars brighter than I = 12, between $4000 \rm K < T_{\rm eff} < 8000 \rm K$ and $0.5 < \rm{log}\,g < 5.0$, RAVE is kinematically and chemically unbiased with respect to expectations from Galaxia.